PROBLEMATIKA PENGGUNAAN TEKNOLOGI TERHADAP PROSES PEMBELAJARAN DAN HASIL BELAJAR SISWA DI ERA REVOLUSI DIGITAL 4.0 - Ella Fizh Asiah; Sahna Maulana Sitakar; Arini Shintha Zahara; Amanda Lestari; Dwi Putri Oktavani Sinabariba (Universitas Negeri Makassar, 2024)
This research aims to describe the problematic use of technology on the learning process and student learning outcomes in the digital revolution 4.0 era. This type of research is descriptive qualitative research. This research uses library research, which is an approach in research that involves in-depth analysis of relevant and pre-existing literature or references to certain research topics. The research data was analysed descriptively qualitatively. The results showed that the use of technology in the learning process led to the inability to think critically, the deterioration of writing skills, and the continuation of passive learning. This has an impact on students' learning outcomes which are low.